Stimulated emission and lasing in Cu(In, Ga)Se2 thin films. (1st February 2016) - Svitsiankou, I E; Pavlovskii, V N; Lutsenko, E V; Yablonskii, G P; Mudryi, A V; Zhivulko, V D; Yakushev, M V; Martin, R W
Abstract: Stimulated emission and lasing in Cu(In, Ga)Se2 thin films have been demonstrated at a temperature of 20 K using excitation by a nanosecond pulsed N2 laser with power densities in the range from 2 to 100 kW cm −2 . Sharp narrowing of the photoluminescence band, superlinear dependence of its intensity on excitation laser power, as well as stabilization of the spectral position and of the full-width at half-maximum of the band were observed in the films at increasing excitation intensity. The stimulated emission threshold was determined to be 20 kW cm −2 . A gain value of 94 cm −1 has been estimated using the variable stripe length method. Several sharp laser modes near 1.13 eV were observed above the laser threshold of I thr ~ 50 kW cm −2 .